Equivalent Test Method for Strong Electromagnetic Field Radiation Effect of EED - Biao Wang; Yongwei Sun; Xuetian Wang; Guanghui Wei; Hongmin Gao (International Journal of Antennas and Propagation)
The present study proposed the equivalent test method for the strong electromagnetic field radiation of electric explosive devices (EEDs) of the weapon equipment to satisfy the military requirements of the electromagnetic radiation safety test, as well as the evaluation of the electric ignition, the electric initiation ammunition, or missiles. Under stable conditions, the ignition excitation test and the bridge wire temperature increase test were performed to determine the ignition temperature of the EED. As radiated by the strong electromagnetic field, the relationship between the temperature increase of the bridge wire and the electric field intensity of the EED was developed based on the theoretical analysis and the experimental test. Given the ignition temperature of the EED, the radiation field intensity of the EED at 50% ignition was determined. As compared with the 50% ignition field intensity of the EED directly radiated by the strong electromagnetic field, an error less than 1 dB was caused. On that basis, the correctness of the equivalent test method was verified. Accordingly, this method was suggested to act as an effective method and technical means to test and evaluate the electromagnetic radiation safety of ammunition and missiles in unfavorable electromagnetic environments.